BAKTERI PELARUT FOSFAT MEMICU KETAHANAN TANAMAN KEDELAI (Glycine max) TERHADAP PENYAKIT SOYBEAN MOSAIC VIRUS - Ni Nyoman Alit Purwaningsih; I Dewa Nyoman Nyana; I Gede Rai Maya Temaja; Gede Suastika (Journal of Agricultural Science and Biotechnology, 2018)
Soybean (Glycine max) is an important commodity in Indonesia. The high utilization of soybean has not been accompanied by the sufficiency of amount of its production, even decreased from year to year. One of the factors that cause the decreased of soybean productivity is soybean mosaic disease caused by viral pathogens. Soybean mosaic virus is one of the most important types of virus in soybean could cause a decreased in yield until 25-90%.This study aimed to test rhizobacteria isolated from the rhizosphere of Leguminosae plants that able to providing resistance to SMV disease on soybean plant. Six isolates rhizobacteria that could be isolated from Leguminosae plants had used as a treatment in the test. The result of field test showed three isolates namely R13, R12, and R9 able to increase soybean plant resistance, so each isolates made influence to crop yield. The results of identification based on the analysis of 16S rRNA gene, isolate R13 which gave the best response to soybean plant resistance and had percentage similarity between 94-98% with species Empedobacter brevis (Flavobacterium breve).